A estrutura curricular em ciclos de aprendizagem nos sistemas de ensino: contribuições de Paulo Freire - Aguiar, Denise Regina da Costa (2011)
The main aim of this research has been on analyzing the proposal of curricular organization inside apprenticeship cycles according to Paulo Freire references inside teaching systems. In order to reach such objective I´ve decided to develop a research on quality purpose starting by the refresh of the knowledge state on the subject of scholar progressions and its cycles (From 1990 up to 2002). The research has been developed through dissertations´ analysis produced from 2003 up to 2008 located in the CAPES database and digital libraries (Ibicit and Domínio Público) besides an illustrative study case in the city of Diadema aiming in analyzing, practically the curricular proposal in apprenticeship cycles inside an emancipation perspective, based on Paulo Freire. In such study case it was used the following procedures: document verification, observation on the side of the participant and interviews performed with members of the Secretaria Municipal de Educação (Education Secretary Department), teachers, students and parents. The precepts and foundations inside apprenticeship cycles which took place in Diadema are focused on Paulo Freire´s work and on the experience developed inside the public education (Municipal Side - São Paulo) during the management of the mayor Luiza Erundina de Sousa (1989-1992). The results of such research here presented demonstrate that the curricular flexibility in apprenticeship cycles based on the emancipated pedagogy (From Paulo Freire side) is a crucial condition to build public, popular and democratic school with social quality. Such study has demonstrated also that it is due to a real and effective participation of all those who really took part of it that could enable the autonomy development of the student. It is about a proposal that need to thrust into state and municipal teaching systems such as the valuable practice of curricular structure for which it is required to always, follow it up and provide assessment aiming in refining it